"For quiet nerves and steady poise": A historical analysis of advertising to New Zealand nurses in the Kai Tiaki Journal 1908-1929. (4th November 2019) - Krisjanous, Jayne; Wood, Pamela
Abstract : Purpose: The purpose of this paper is to examine advertising placed within Kai Tiaki: The Journal of Nurses of New Zealand . The periodization for this study is 1908-1929, a chronological time span and approach that incorporates the first issue of the Kai Tiaki in 1908 and ending 1929, thus representing the launch of the journal and first two decades of its production. During this period, New Zealand nursing was emerging as an organised and professionalised body of health-care workers. At the same time, New Zealand, Britain's most distant "dominion", was beginning to realise its own nationhood and growth. Design/methodology/approach: The primary source of data was digitalised Kai Tiaki issues between 1908 and 1929. Each four issues for every year were analysed. All advertisements were coded ( n = 1895), followed by a qualitative content analysis in which key themes were derived. Findings: Five overarching themes were found. The two main themes were the proliferation of therapeutic "tonics" and the second the relationship of nurses to them that was profiled by advertisers. The three remaining themes were accommodations, lifestyle and the nurses "role" as nurse, handmaiden or mother. Conclusions discuss reasons for key findings, and, in particular, the reinforcement of the traditional nursing role, which was often at odds with the increased technological roles and responsibilities nurses were undertaking. In turn, advertisers saw the nursing profession as a new and potentially lucrative market of women with disposable income and influence in the health field. Originality/value: To date, there is a scarcity of marketing analysis that examines advertising placed in trade journals and in particular for early twentieth century health-care professionals. Through a lens of advertising analysis, this study investigates the advertising nursing readership of the day was exposed to and the motives and tactics used by those interested in expanding both health-care worker and consumer markets through a singular strategy.